2022
DOI: 10.3831/kpi.2022.25.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia annua L. Extracts Improved Insulin Resistance via Changing Adiponectin, Leptin and Resistin Production in HFD/STZ Diabetic Mice

Abstract: Objectives: Insulin resistance (IR) is major cause of type 2 diabetes (T2D), and adipokines (e.g., adiponectin, leptin, and resistin) play an important role in insulin sensitivity. Medicinal plants are frequently used for T2D treatment. This study investigates the effect of Artemisia annua L. (AA) extracts on adipokines in mice with high-fat-diet (HFD)/streptozotocin (STZ)-induced T2D. Methods: We divided 60 mice into 12 groups (n = 5 per group): control, untreated T2D, treated T2D, and 9 other groups. T2D was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…In testis tissues, the results of Artemisia annua showed normal spermatic tubules with active spermatogenesis reaching spermatozoa stage in all treated and non-treated animal groups. In the previous studies, the histopathology indicating that the liver was not adversely affected by EAA further confirmed the earlier statements that EAA may not be toxic to the liver [ 19 , 20 ]. While, [ 22 ] has found that the acute administration of large doses of pioglitazone (Actos drug) caused ventricular hypertrophy with congestion of liver in mice which can happen with accidental over dose of pioglitazone in patients.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In testis tissues, the results of Artemisia annua showed normal spermatic tubules with active spermatogenesis reaching spermatozoa stage in all treated and non-treated animal groups. In the previous studies, the histopathology indicating that the liver was not adversely affected by EAA further confirmed the earlier statements that EAA may not be toxic to the liver [ 19 , 20 ]. While, [ 22 ] has found that the acute administration of large doses of pioglitazone (Actos drug) caused ventricular hypertrophy with congestion of liver in mice which can happen with accidental over dose of pioglitazone in patients.…”
Section: Discussionsupporting
confidence: 83%
“…In related previous studies, [ 19 ] has found no changes in the liver (ALT and AST) and kidney (urea and Creatinine) functions in all the EAA-treated ( Artemisia Annua Ethanol extract) groups compared to the control group and the author recommended that EAA treatment may not predispose the users of this plant to hepatotoxicity and renal dysfunction. Concerning glucose, different types of AA extracts were used by [ 20 ] to improve insulin resistance through reduction of TNF-alpha. These previous results confirm our findings that higher levels of bioactive components might be present in the higher concentrations of Artemisia extracts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of C. papaya brought down the levels of these adipocytokines close to normalcy, such as that of standard drug treated group. Likewise, Ghanbari, et al [51] reported that aqueous and alcoholic extracts of Artemisia annua L. augmented the insulin resistance in high fat diet-streptozotocin induced T2DM mice with a surge in adiponectin and diminution in leptin and resistin production in fat cells. Ansari et al and his co-workers reported in their work the effect of synthesized gold nanoparticles from Smilax glabra that modulated the levels of serum leptin and adiponectin in high fat diet-streptozotocin induced rat models [52].…”
Section: Discussionmentioning
confidence: 97%
“…Artemisinin has been recognized as a potent and effective antimalarial drug that has been widely applied in the world [43]. Beyond anti-parasite activity, artemisinin and its derivatives exhibit the therapeutic potentials for viral infections, inflammatory disease, autoimmune diseases and cancer [44][45][46][47]. Also, the extracts of Artemisia annua, particularly artemisinin and flavonoids, have been reported to have numerous pharmacological properties [48,49].…”
Section: Discussionmentioning
confidence: 99%